From open government to open parties in Europe. A framework for analysis - Villaplana, F. Ramón; Megías, Adrián; Sandri, Giulia (Frontiers in Political Science, 2023)
Open Government is an increasingly used management model among public administrations of European countries and of the European Union, which is currently working on The Path to the Digital Decade. That supposes applying measures to promote proximity and citizenship’s prominence in many public policies, leading to improved quality of democracy. Furthermore, the Covid-19 pandemic has contributed to a forced digitalisation of many public services. Despite the fact that studies on OG do not usually focus on them, political parties are essential actors for the success or failure of OG measures, both from a bottom-up and a top-down perspective on public administration transformation. Moreover, political parties are transforming themselves into more open organisations at the same time. We define open parties as political parties with high standards in transparency, participation and collaboration. They also feature high degrees of organisational digitalisation. This paper proposes a framework for analysing political parties’ openness and explores available empirical data on different aspects related to OG in the European context. We found that most of parties possess a good level of local organisational strength but still need to reach better levels of anticorruption commitment, stronger ties to affiliated organizations and especially need to improve the participation of members and activists in their decision-making. Furthermore, elitism, clientelism and populistic rhetoric represent significant obstacles that could hinder the party reform process.